Emerging roles of Axin in cerebral cortical development - Ye, Tao; Fu, Amy K. Y.; Ip, Nancy Y. (Frontiers in Cellular Neuroscience, 2015)
Proper functioning of the cerebral cortex depends on the appropriate production and positioning of neurons, establishment of axon–dendrite polarity, and formation of proper neuronal connectivity. Deficits in any of these processes greatly impair neural functions and are associated with various human neurodevelopmental disorders including microcephaly, cortical heterotopias, and autism. The application of in vivo manipulation techniques such as in utero electroporation has resulted in significant advances in our understanding of the cellular and molecular mechanisms that underlie neural development in vivo. Axin is a scaffold protein that regulates neuronal differentiation and morphogenesis in vitro. Recent studies provide novel insights into the emerging roles of Axin in gene expression and cytoskeletal regulation during neurogenesis, neuronal polarization, and axon formation. This review summarizes current knowledge on Axin as a key molecular controller of cerebral cortical development.